Robust Multi-Objective Control of Power System Stabilizer Using Mixed H2/H∞ and µ Analysis - Javad Mashayekhi Fard (Institute of Advanced Engineering and Science, 2018)
In order to study the dynamic stability of the system, having a precise dynamic model including the energy generation units such as generators, excitation system and turbine is necessary. The aim of this paper is to design a power stabilizer for Mashhad power plant and assess its effects on the electromechanical fluctuations. Due to lack of certainty in the system, designing an optimized robust controller is crucial. In this paper, the establishment of balance between the nominal and robust performance is done by the weight functions. In the frequencies where the uncertainty is high, in order to achieve to the robust performance of the controller, μ analysis is more profound, otherwise, in order to achieve to nominal performance, robust stability, noise reduction and decrease of controlling signal, the impact of the controller H2/H∞ is more profound. The results of the simulation studies represent the advantages and effectiveness of the suggested method.